Pembelajaran Daring Dosen Native Tiongkok terhadap Mahasiswa FKIP Universitas Tanjungpura - Lily Thamrin (LP4MK STKIP PGRI Lubuklinggau, 2020)
Online learning during the Covid-19 pandemic has become a substitute solution for face-to-face learning. For this reason, the purpose of this study is to describe the online learning process, problems in online learning, and online learning strategies that are applied to Comprehensive Chinese Language Courses. This research method using mixed methods. Data collection techniques using observation techniques, questionnaires, and interviews. The respondents of this study were 90 people consisting of first, third, and five semester students of the Mandarin Education Study Program, the Teaching and Education Faculty, Universitas Tanjungpura, and 4 native lecturers from China. The results showed that native lecturers in the online learning process used the Ding Talk and Tencent (VooV) Meeting applications. Learning media used such as computers, laptops, and smartphones as well as internet networks are available but are not fully utilized in the online learning process. Meanwhile, the obstacles faced during online learning are the network problems used by students. The network used by students to take part in online learning is very unstable, resulting in students often going in and out of this online learning platform. To solve the problems that occur, lecturers often use a question and answer strategy to get feedback from students. There are also lecturers who use their spare time to individually guide students who are deemed lacking in learning.